2021
DOI: 10.1111/pai.13543
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric problematic severe asthma: Recent advances in management

Abstract: Asthma is a chronic airways disease with both immediate and longterm health implications, including death and permanent disability.The burden of asthma, both clinical and financial, is considerable, with more than 100,000 annual hospital admissions in the United Kingdom and an overall cost of more than £1 billion per annum to the NHS. 1 A significant proportion of these costs can be attributed to children with asthma, in particular, those with severe asthma, who utilize up to 50% of healthcare resources for as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 99 publications
0
6
0
1
Order By: Relevance
“…Non-Th2 asthma (i.e., neutrophilic asthma), by contrast, is characterized by high levels of IFN-γ and IL-17, along with airway neutrophilic infiltrate ( 36 ). Recent studies have increasingly shown that severe childhood asthma is associated with neutrophils ( 37 , 38 ). In this study, the asthma mice showed increased Th1- and Th17-type responses and neutrophils in lungs, and no detectable IgE in sera, which is similar to the no-Th2 asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Non-Th2 asthma (i.e., neutrophilic asthma), by contrast, is characterized by high levels of IFN-γ and IL-17, along with airway neutrophilic infiltrate ( 36 ). Recent studies have increasingly shown that severe childhood asthma is associated with neutrophils ( 37 , 38 ). In this study, the asthma mice showed increased Th1- and Th17-type responses and neutrophils in lungs, and no detectable IgE in sera, which is similar to the no-Th2 asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Rezultati pretraga induciranog sputuma, BAL-a i endobronhalne biopsije pokazuju najčešće eozinofi lnu, a u neke djece paucigranulocitnu (nema porasta broja ni eozinofi la, ni neutrofi la) upalu uz patološke naznake remodelacije bronha. Međutim, nalaz stanica u induciranom sputumu, BAL-u i u sluznici bronha nije ujednačen u svih bolesnika (11). S obzirom na dominaciju eozinofi la u bioptatu bronha, očekivani nalaz citokina upale tipa 2 -IL-4, IL-5 i IL-13 nije potvrđen u sluznici bronha kod djece, za razliku od odraslih bolesnika (12,13).…”
Section: Invazivni Biomarkeri U Procjeni Upale U Dišnom Putuunclassified
“…In particular, dupilumab, a fully human mAb directed toward the alpha chain of the IL-4 receptor used by both IL-4 and IL-13, is the first and only biological agent approved for the treatment of CRSwNP in adults with type 2 inflammation, regardless of the presence of asthma as a comorbidity, due to its effectiveness in reducing polyp size, sinus opacification, and symptom severity [45,64,88]. Dupilumab is also approved for the treatment of severe type 2 asthma, starting from 12 years of age [89]. There is still limited evidence on the efficacy of omalizumab (an anti-IgE) and mepolizumab (anti-IL-5) in CRSwNP, mainly in adult patients with comorbid asthma [90,91]; both of these drugs are currently approved for children aged ≥6 years with severe asthma.…”
Section: Treatment Of Nasal Polyps: the New Era Of Biological Agentsmentioning
confidence: 99%